Penerapan Repacking pada Produk Rengginang Masagena di Kecamatan Konda - Syahruddin, Syahruddin; Hamid, Ahmad; Jasman, Jasman; Purwitasari, Paramitha; Kasim, Hasdi Syahid; Menungsa, Abdul Sarlan; Juliana, Andi; Cahyani, Roro (Abdimas Universal, 2025)
Rengginang is a food that tends to be enjoyed by people in various regions, both urban and rural, because the price is cheap and accessible to all groups. Rengginang Masagena is one of the commercial products in Masagena Village, Konda District, which is produced by a community business group. However, the obstacle faced by this group is the lack of understanding of partners to improve the quality of packaging so that product sales slow down. This can be done especially to increase community income. The implementation of this service aims to help partners improve their knowledge and quality of packaging through training and direct materials. The results of the community service show that the knowledge and understanding of partners has increased significantly regarding the benefits of using standing pouches as new packaging to replace previously used plastic bags, and the knowledge of partners regarding their use. Likewise with the use of vacuum equipment and packaging presses used in rengginang packaging where partners improve in terms of understanding and direct practice, then partners also understand how to design and create brands/brands in packaging so that partners have products that have brands that ultimately the team hopes that partners can improve the quality and sales of rengginang products.